JAJAK PENDAPAT TIMOR TIMUR DALAM PERSPEKTIF PERLINDUNGAN HUKUM MASYARAKAT SIPIL PASCA KONVENSI JENEWA 1949 - Lorraine Rangga Boro (Faculty of Law, Universitas Diponegoro, 2014)
This study aims to determine the dedermination of East Timor in the perspective of the legal protection of civilians after the Geneva Convention of 1949. This study is a normative law. The method used is the approach Statute and Conceptual approach. Results of the study found that First , there is no post- Civil Legal Protection East Timor According to the 1949 Geneva Convention (IV Geneva Convention Concerning the Protection of Civilian Persons in war) . Second , the Indonesian government be held accountable law violations against the self determination of East Timor in 1999